Perbedaan Individual dan Konsekuensinya Bagi Pembelajaran Bahasa Indonesia - Muhammad Hasbullah Ridwan; Siti Nur Afifatul Hikmah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2021)
Every learner has a different way of adapting and understanding instructions, especially in language learning. Cognitive abilities possessed by each individual are intelligence, language learning talent, or memory capacity or speed. In addition, affective abilities such as fear, motivation, and emotions of an individual. Research on individual differences can be seen from the interaction or relationship of the two aspects in humans and also to the context of learning, individual understanding naturally of an instruction can be identified properly. Every learner has a different way of adapting and understanding instructions, especially in language learning. First, individual differences consist of two factors, namely personal factors and general factors. Personal factors include (1) group dynamics, (2) attitudes towards teachers and teaching materials, and (3) individual learning techniques, while general factors include (1) age, (2) intelligence and dexterity, (4) cognitive-style, (5) attitude and (6) motivation, and (7) personality. Second, the consequences of individual differences for learning Indonesian in this discussion relate to the way educators teach. Third, related to learning components (learning resources, teaching materials, learning strategies, and assessments).